Synergistic associations of depressive symptoms and aging on cognitive decline in early Parkinson’s disease - Lea Hemphill; Yenny Valenzuela; Kenya Luna; Sarah M. Szymkowicz; Jacob D. Jones (Clinical Parkinsonism & Related Disorders, 2023)
Objective: Parkinson's disease (PD) is the second most common progressive neurodegenerative disorder. About 40%–50% of PD patients experience depression, making it one of the most common neuropsychiatric disturbances in PD. Cognitive deficits (e.g., difficulties with memory, attention) are an additional common complication in PD. Past studies among healthy aging individuals suggest that depression is a risk factor for cognitive decline, and the risk increases with older age. This study aims to examine the association between depressive symptoms on cognitive decline as a function of age among patients with PD. It is hypothesized that older PD patients with more severe depressive symptoms will be at greater risk of cognitive decline than their younger or less depressed counterparts. Methods: Four hundred and eighty-seven newly diagnosed patients with PD, were assessed for depression and cognition over a five-year period. Participants completed neuropsychological tests that assessed memory, learning, attention, visuospatial functioning, processing speed, and verbal fluency. Multilevel-modeling was used to examine the longitudinal association between cognition, age, and depressive symptoms. Results: Our results indicated a significant three-way interaction (age X occasion X depressive symptoms) predicting language and working memory/attention performance. More specifically, detrimental associations of depressive symptoms on cognitive decline in these domains were more pronounced among older adults. Conclusions: Our findings support that older PD patients with comorbid depressive symptoms experience greater cognitive decline compared to their younger counterparts. Findings suggest that older individuals with PD may be more vulnerable to neurotoxic effects of depression (e.g., neuroinflammation, HPA axis disruption), and better management of depression could potentially reduce cognitive decline and dementia risk.